2014
DOI: 10.1016/j.mod.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic dissection of myogenic differentiation signature in caprine by RNA-Seq

Abstract: Muscle growth and development from the embryonic to the adult stage of an organism consists of a series of exquisitely regulated and orchestrated changes in expression of genes leading to muscle maturation. In this study, we performed whole transcriptome profiling of adult caprine skeletal muscle derived myoblast and fused myotubes. Using Ion Torrent PGM sequencing platform, a total of 948,776 and 799,976 reads were generated in myoblasts and fused myotubes, respectively. The sequence reads were analyzed on CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
5
11
0
Order By: Relevance
“…Quantitative transcriptome analysis identified 549 upregulated genes and 614 downregulated genes during early stages of neurodevelopment. As expected, and in agreement with changes observed in other differentiating cell types, GO term enrichment analysis showed strong downregulation of genes related to cell proliferation during terminal differentiation Gao, Yourick, and Sprando 2014;Tripathi et al 2014). Simultaneously, genes related to neurodevelopmental processes such as neurite formation and axonogenesis are upregulated, which is in line with changes previously observed in mouse iPSCs and human ESCs (Wu et al 2010;Chen et al 2013).…”
Section: Quantitative Profiles Of Transcriptomic and Proteomic Of Earsupporting
confidence: 89%
“…Quantitative transcriptome analysis identified 549 upregulated genes and 614 downregulated genes during early stages of neurodevelopment. As expected, and in agreement with changes observed in other differentiating cell types, GO term enrichment analysis showed strong downregulation of genes related to cell proliferation during terminal differentiation Gao, Yourick, and Sprando 2014;Tripathi et al 2014). Simultaneously, genes related to neurodevelopmental processes such as neurite formation and axonogenesis are upregulated, which is in line with changes previously observed in mouse iPSCs and human ESCs (Wu et al 2010;Chen et al 2013).…”
Section: Quantitative Profiles Of Transcriptomic and Proteomic Of Earsupporting
confidence: 89%
“…In goat skeletal muscle, the main focus has been on genes and miRNAs rather than on lncRNAs [44, 45, 50, 51]. In the present study, we identified a total of 3981 multiple exon lncRNAs in fetal and postnatal goat skeletal muscle.…”
Section: Discussionmentioning
confidence: 83%
“…Regardless, we have shown that RNA-seq quality metrics and bias removal can successfully be utilized on multiple platforms. Because many aspects of library preparation and normalization are universal aspects of working with RNA, including isolation, purification, priming, amplification, reagent batch and kit version, the recommendations and most of our observations presented here will likely be applicable to any sequencing platform used for RNA-seq 46,47 .…”
Section: Discussionmentioning
confidence: 99%